Hot tear resistance of vulcanized rubber / Nor Atiqah Kamarudin - Kamarudin, Nor Atiqah (2015)
Molding is a process to fabricate the compounded rubber to the desired shape and dimensions of the intended product. Rejects attributed to poor hot tear resistance of vulcanized rubber at high temperature vulcanization are of prime concerned, in particular thin and complicated moulded rubber profiles. The purpose of this study is to investigate the effect of high temperature on tearing energy of vulcanized rubber, the effect of types of filler on tearing energy and the effect of types of crosslink on hot tear resistant. Tearing measurements were done at various different temperatures practiced by the rubber industry. Trouser test-pieces were placed inside an electrically heated oven at the desired test temperature for 15 minutes before applying dead load to determine its critical tearing energy. It was found that strain-crystallizing rubbers showed critical tearing energy, Tc. Above Tc catastrophic tearing occurs. Non-strain-crystallizing rubber shows time dependent tearing where the crack increases in length as a function of time. The magnitude of tearing energy is affected by the extend of strain-crystallization. In the absence of strain-crystallization, the tearing energy is affected by the glass-transition temperature, Tg. The higher the Tg, the higher is the tearing energy.